English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

Uh, no, the correct identity is ln (x/3) = ln x - ln 3. The only way ln (x-3) = ln x - ln 3 is if x-3 = x/3, i.e. if x=9/2.

2007-12-16 15:47:21 · answer #1 · answered by Pascal 7 · 1 1

This is NOT true for all values of x. It is true only if x = 9/2 as worked out below.

ln(x)-ln(3) = ln (x/3)
For the given statement to be true
x - 3 = x/3
=> x = 9/2

2007-12-16 23:45:35 · answer #2 · answered by Madhukar 7 · 0 2

your assumption is not valid.
ln(x/3) = ln(x) -- ln(3).

2007-12-16 23:50:08 · answer #3 · answered by sv 7 · 0 1

first the way you formulated the question does not make sense
you say "suppose" something. If you suppose then you assume already that it is true.

2007-12-16 23:52:58 · answer #4 · answered by Theta40 7 · 0 1

fedest.com, questions and answers